Alternative end-joining catalyzes robust IgH locus deletions and translocations in the combined absence of ligase 4 and Ku70 - Boboila, Cristian (National Academy of Sciences, 2010)
Class switch recombination (CSR) in B lymphocytes is initiated by introduction of multiple DNA double-strand breaks (DSBs) into switch (S) regions that flank immunoglobulin heavy chain (IgH) constant region exons. CSR is completed by joining a DSB in the donor Sμ to a DSB in a downstream acceptor S region (e.g., Sγ1) by end-joining. In normal cells, many CSR junctions are mediated by classical nonhomologous end-joining (C-NHEJ), which employs the Ku70/80 complex for DSB recognition and XRCC4/DNA ligase 4 for ligation. Alternative end-joining (A-EJ) mediates CSR, at reduced levels, in the absence of C-NHEJ, even in combined absence of Ku70 and ligase 4, demonstrating an A-EJ pathway totally distinct from C-NHEJ. Multiple DSBs are introduced into Sμ during CSR, with some being rejoined or joined to each other to generate internal switch deletions (ISDs). In addition, S-region DSBs can be joined to other chromosomes to generate translocations, the level of which is increased by absence of a single C-NHEJ component (e.g., XRCC4). We asked whether ISD and S-region translocations occur in the complete absence of C-NHEJ (e.g., in Ku70/ligase 4 double-deficient B cells). We found, unexpectedly, that B-cell activation for CSR generates substantial ISD in both Sμ and Sγ1 and that ISD in both is greatly increased by the absence of C-NHEJ. IgH chromosomal translocations to the c-myc oncogene also are augmented in the combined absence of Ku70 and ligase 4. We discuss the implications of these findings for A-EJ in normal and abnormal DSB repair.